A Content Analysis on Management Fashions in Turkish Manufacturing Companies - Yaşar Uğurlu, Özlem; İbrahimoğlu, Nurettin; Ayas, Sibel (International Review of Management and Marketing, 2013)
Recently many scholars have paid attention to the concept of management fashions as a new field in organization studies. This research aims to emphasize the awareness of organizations about management fashions and how strongly organizations adopt new management approaches. As a qualitative research a content analysis was applied. Data was obtained from web sites of 79 companies based on the first 500 businesses according to the data of Istanbul Chamber of Industry (2011) and also were listed in Exchange Istanbul’s Industrial index (XUSIN). The findings have shown that strategic management, HRM and TQM are practiced more than organizational learning, innovation and ethics/social responsibility. Theoretical and practical implications are also discussed. Keywords: Management fashions; new management approaches; content analysis JEL Classifications: M10